Gender, Military Effectiveness, and Organizational Change - Egnell, R. author. aut Link
XI, 185 p.
Keywords: Through extensive analysis of the Swedish Armed Forces this study explores the possibilities and pitfalls of implementing of a gender perspective in military organizations and operations. It established a number of important lessons for similar attempts in other countries and discusses the continued process of implementation in the Swedish military.